2014
DOI: 10.1038/ncomms4361
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptome profiling of homologous recombination DNA repair

Abstract: Homologous recombination (HR) repair deficiency predisposes to cancer development, but also sensitizes cancer cells to DNA-damage-inducing therapeutics. Here we identify an HR-defect (HRD) gene signature, which can be used to functionally assess HR repair status without interrogating individual genetic alterations in cells. By using this HRD gene signature as a functional network analysis tool, we discover that simultaneous loss of two major tumor suppressors BRCA1 and PTEN extensively rewire the HR repair-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
218
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(234 citation statements)
references
References 48 publications
14
218
1
1
Order By: Relevance
“…HDAC inhibitors induce hyperacetylation of HSP90 and dissociate client proteins, such as BRCA1, from the chaperone. In vitro studies have also demonstrated that HDAC inhibitor vorinostat and HSP90 inhibitor AUY922 were ranked near the top for inducing the HRD-like gene expression profiles in TNBC cell lines [118].Thus, treatment with HDAC inhibitors can increase the therapeutic efficacy of DNA-damaging agents, such as platinum compounds in TNBC. Indeed, in vitro studies show that cotreatment with a pan-HDAC inhibitor and cisplatin synergistically induced apoptosis of both BRCA1-mutant and BRCA1-proficient cell lines and HDAC inhibitor treatment induces synergistic lethality with PARPi and cisplatin in triple-negative breast cancer cell lines [119][120][121].…”
Section: Heat Shock Protein 90 and Histone Deacetylase Inhibitorsmentioning
confidence: 98%
“…HDAC inhibitors induce hyperacetylation of HSP90 and dissociate client proteins, such as BRCA1, from the chaperone. In vitro studies have also demonstrated that HDAC inhibitor vorinostat and HSP90 inhibitor AUY922 were ranked near the top for inducing the HRD-like gene expression profiles in TNBC cell lines [118].Thus, treatment with HDAC inhibitors can increase the therapeutic efficacy of DNA-damaging agents, such as platinum compounds in TNBC. Indeed, in vitro studies show that cotreatment with a pan-HDAC inhibitor and cisplatin synergistically induced apoptosis of both BRCA1-mutant and BRCA1-proficient cell lines and HDAC inhibitor treatment induces synergistic lethality with PARPi and cisplatin in triple-negative breast cancer cell lines [119][120][121].…”
Section: Heat Shock Protein 90 and Histone Deacetylase Inhibitorsmentioning
confidence: 98%
“…DSB-bound Ku then recruits and activates the DNA-dependent protein kinase catalytic subunit (DNA-PKcs), which triggers a signaling cascade that orchestrates downstream repair processes that eventually seal the breaks (7). In the HR repair pathway, DSBs are recognized by the MRN (Mre11-Rad50-NBS1) complex and CtIP to initiate DSB end resection leading to generation of 3′ single-stranded DNA (ssDNA) overhangs through endonucleolytic cleavage followed by 3′-5′ exonucleolytic processing (6,8,9). The 3′ ssDNA overhangs are initially coated by the RPA complex to form an RPA-ssDNA nucleoprotein filament to allow extensive resection by the EXO and DNA2 nucleases, followed by displacement of RPA to allow assembly of the Rad51-ssDNA nucleoprotein filament (1).…”
Section: Introductionmentioning
confidence: 99%
“…2D). Because previous work shows that BRIT1 depletion does not impact the percentage of cells in S phase (27,30), we infer that the reduction in Ser(P)-33-RPA32 signal at later time points is not due to cell cycle changes resulting from BRIT1 depletion. Together, these data indicate that BRIT1 is not required for initial ATR activation but may be required for establishing a positive feedback loop to amplify ATR signaling.…”
Section: Brit1 Is Required For Sustained Rpa Phosphorylation and May mentioning
confidence: 99%